The Effect Of Financial Literacy And Financial Attitudes On Interest In Using Spinjam In Shopee E-Commerce On Students Of The Faculty Of Economics And Business Bandar Lampung University - Ningrum, Yessy Septia; Habiburrahman, Habiburrahman (LPPPIPublishing, 2023)
The purpose of this research is to test how much financial literacy and financial attitudes contribute to interest in using SPinjam on the Shopee platform. The objects of this research were FEB students at Bandar Lampung University. Primary data was collected from students by distributing questionnaires to 76 respondents online using a Likert Scale. The accepted sampling method is a probability technique with an emphasis on simple random sampling. By analyzing the data using multiple linear regression analysis via SPSS Statistics 26, the results of the analysis show that financial literacy has a significant effect on interest in using SPinjam, as evidenced by the sig. 0.035 < 0.05. On the other hand, financial attitudes do not show a significant effect on interest in using SPinjam, seen from sig. 0.210 > 0.05. However, when financial literacy and financial attitudes are examined simultaneously, both have a significant impact on interest in using SPinjam, with sig. 0.003 < 0.05.